Reduction Inverts the Thermodynamics of the Stone–Wales Rearrangement - Daniel Čavlović; Jacklin H. Smith; Scott R. Docherty; Shayan Louie; Xavier Roy; Michael L. Steigerwald; Colin P. Nuckolls (Journal of the American Chemical Society, 2026)
Abstract We demonstrate that alkali-metal doping of polycyclic aromatic hydrocarbons can reshape the potential energy surface in favor of an isomer that is disfavored in the neutral state. This effect enables an efficient inverse Stone–Wales rearrangement at temperatures as low as 250 °C for potassium-, rubidium-, and cesium-doped systems. In contrast, lithium and sodium doping exclusively promote cyclodehydrogenation at cove regions. Supported by density functional theory, we propose a mechanistically consistent pathway and report the isolation and characterization of key anionic intermediates by single-crystal X-ray diffraction, UV–vis spectroscopy, and magnetometry. These findings highlight how reduction can unlock otherwise inaccessible rearrangements in aromatic systems and inform our understanding of the functionalization of graphene, carbon nanotubes, and fullerenes.